Eksistensi Usaha Kecil Menengah dan Pasar Tradisional dalam Kebijakan Pengembangan Pasar Modern - Dakhoir, Ahmad (Jurnal Studi Agama dan Masyarakat, 2018)
The growing rapidly of modern market in the mid of traditional markets and Small Medium Enterprises has not become energy and instruments in the development of people's economy in Indonesia. The number of modern retailers should also be utilized by small medium businessmen. This paper is aimed at explaining the existence of Small Medium Enterprises (SMEs) and traditional markets amid the rapidly development of modern market. The dynamic is also felt by SMEs and traditional markets in Palangkaraya Town, Central Kalimantan. The method of this study uses descriptive qualitative approach. The object of study is all markets / modern stores and traditional markets in Palangka Raya Town. Based on the results of the analysis, this study reveals that the establishment of modern stores in Palangka Raya Town has a positive impact in the Palangka Raya Town. It becomes one of the factors encouraging the social and economic growth of the city. While the negative impact is that it threatens the resilience of traditional shops / markets and the similar small businesses and it can trigger social vulnerability (unharmonious).